Athermal and Soft Multi‐Nanopatterning of Azopolymers: Phototunable Mechanical Properties. (9th January 2020) - Yang, Bowen; Cai, Feng; Huang, Shuai; Yu, Haifeng
Abstract: Imprinting nanopatterns on flexible substrates has diverse applications in advanced fabrication. However, the traditional thermal nanoimprint lithography (T‐NIL) often causes shrinkage upon cooling. Here, a simple yet versatile method is introduced to fabricate multiple nanopatterns on a flexible substrate coated with an azopolymer by combining athermal nanoimprint lithography (AT‐NIL) and photolithography. The azopolymer has various mechanical properties upon photoirradiation: 1) phototunable glass‐transition temperatures ( T g ) and concomitantly photoinduced switch from glassy plastic to viscoplastic polymer; 2) prominent modulation of viscoplasticity under light illumination at different wavelengths. Regionally selective multiple nanopatterns are conveniently fabricated, presenting angle‐dependent structural color images on poly(ethylene terephthalate) (PET) substrates. The flexible, athermal and multiple nanopatterning method has the potential for on‐demand fabrication of complex nanopatterns. Abstract : Die Mechanik eines Azopolymers kann durch Lichteinstrahlung feinjustiert werden, einschließlich einer photoschaltbaren Glasübergangstemperatur und dem photoinduzierten Wechsel von glasartigem Plastik zu einem viskoplastischen Polymer. Die abstimmbaren mechanischen Eigenschaften ermöglichen die Herstellung von Nanomustern auf flexiblen Substraten durch die Kombination von athermischer Nanoimprint‐Lithographie und Photolithographie.